Method and Application of Urban 3D Rapid Modeling of Geology Based on CAD Borehole Logs - Xuefeng Zhang; Cheng Chen; Zifei Xu; Hong Li (Geofluids)
Urban 3D geological modeling is one of the key technologies of geological data visualization and spatial analysis. Aiming at the problems of cumbersome modeling process, low modeling efficiency, and accuracy of traditional modeling methods based on borehole data, in this paper, a fast 3D geological modeling method based on CAD borehole data is proposed. The method first designed a method for rapidly extracting borehole log information which is based on .Net API (c#). On this basis, knowledge-driven 3D geological modeling method based on profile data is employed. With these methods, the borehole data in CAD format can be converted to structured data, which can be directly used for data analysis, and the geological knowledge can be analyzed and integrated into the process of three-dimensional geological modeling. The feasibility of this method is verified using the CAD borehole data in the West District of Kaifeng City as an example. The results show that this method can not only realize the rapid construction of urban 3D geological model but also improve the accuracy of 3D geological model.